(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the importance of teamwork between lab technicians and nurses in the healthcare setting. Lab technicians and nurses play distinct yet interdependent roles in providing patient care, with their collaboration significantly impacting patient outcomes. Through effective communication and mutual reliance, lab technicians and nurses facilitate timely diagnostic testing, informed decision-making, and coordinated patient care. Recognizing and appreciating the contributions of both professions fosters a culture of collaboration, enhancing workplace morale and ultimately improving patient satisfaction and outcomes.